Client‐based project work as experiential education. (23rd April 2019) - Jacobs, Jessica
Abstract : The student practicum is a time‐honored part of design education. That's why it's so surprising that very little research has been done into the pedagogy, design, operations, and assessment of this type of "experiential education." Most design schools include some kind of studio practicum course in which educators seek to create "real world" projects with external clients. Do these experiences lead to an increase in student understanding of design management practices? How do educators assess these projects?